STUDI KELAYAKAN BISNIS UMKM MOYI SALON: ASPEK PASAR DAN PEMASARAN, TEKNIS DAN OPERASIONAL, DAN MANAJEMEN - Titi Nurhayati Luhulima; Christina Sososutiksno; Pranatalindo Simanjuntak; Nopita Sirait; Sarlina Samal; Ana Marsya Ode; Fanesa Aulana Laisouw; Nadia Indra (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Moyi Salon is a beauty salon that has experienced rapid growth over the past few months, making a business feasibility study essential to evaluate its success and the challenges it faces. This study aims to examine how Moyi Salon utilizes and manages marketing, managerial, and operational elements in running its business activities. The research adopts a descriptive qualitative approach using a case study method to provide an in-depth and comprehensive understanding of the business. Data were collected through direct observation at the business location, supporting documentation, and interviews with the owner and relevant stakeholders. The collected data were then analyzed systematically to assess the feasibility of the business from each examined aspect. The results indicate that Moyi Salon is feasible to operate and has strong potential for further development in the beauty industry, as it meets the feasibility criteria across marketing, managerial, and operational aspects. The findings of this business feasibility analysis are expected to serve as a basis for formulating appropriate strategies to support business growth and achieve long-term sustainability and success.